(untitled) (Research, Society and Development, 2026)
Major Depressive Disorder (MDD) is a psychiatric condition characterized by prolonged episodes of a combination of symptoms such as depressed mood and loss of interest. It may be triggered or intensified by various factors, among which oxidative stress and its associated chemical dysregulations stand out. The objective of this review is to explore antioxidant therapeutic approaches with the potential to contribute to the improvement of mental health in patients with Major Depressive Disorder through modulation of physiological antioxidant functioning. The review was conducted using the PubMed, Scielo, and LILACS databases, based on the following DeCS terms: ("oxidative stress" or "oxidative injury" or "oxidative cleavage") and ("depression" or "major depressive disorder"), resulting in 73 articles for analysis, of which 15 were included in this review after applying exclusion criteria in two stages. The analyzed studies highlight the effectiveness of different antioxidant interventions in reducing oxidative stress markers associated with depression. Among these approaches, the use of pharmacological agents such as N-acetylcysteine and thymoquinone, natural extracts such as Caesalpinia pulcherrima and ayahuasca, as well as supplementation with probiotics and fatty acids (omega-3, 6, and 9), are noteworthy. Positive effects were also observed from non-pharmacological strategies such as the adoption of antioxidant-rich diets, physical exercise, and repetitive transcranial magnetic stimulation. These interventions demonstrated antidepressant potential by modulating oxidative stress, although further studies are needed to assess their long-term efficacy.